Hemicellulose Biomass Degree of Acetylation (Natural Versus Chemical Acetylation) as a Strategy for Based Packaging Materials - Martins, Júlia Ribeiro [UNESP]; Llanos, Jaiber Humberto Rodriguez [UNESP]; Botaro, Vagner; Gonçalves, Adilson Roberto [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2024)
Facing increasing social, environmental, and economic pressure to substitute non-renewable fossil resources with renewable ones, hemicellulose has received attention as a substrate for the production of high-value products such as packaging materials because of its non-toxicity, abundance, and biodegradability. Hemicelluloses in the cell wall are naturally substituted with acetyl groups, and the degree and pattern of acetylation vary among plant species, tissue and cell types, and plant maturity. Hemicellulose acetylation influences features such as the flexural properties of wood, polysaccharide interactions, plant growth, and stress resistance. However, hemicellulose is deacetylated during its separation from other biomass polymers, mainly via alkaline solubilization. Therefore, when industrial applications require a certain degree of acetylation, chemical acetylation is necessary, which occurs through an esterification reaction that links acetyl groups to hemicellulose, catalyzed or not. Acetylation may enhance some features of hemicellulose-based packaging materials, such as mechanical strength, processability, thermal stability, hydrophobicity, and oxygen and water vapor permeability. This review provides an update on the latest advances in plant polysaccharide acetylation, including the acetylation mechanism in the plant cell wall as well as the influence of such esterification on plant properties and wood industrial application. Recent developments and progress in hemicellulose chemical acetylation strategies have been summarized, disclosing the advantages and disadvantages of different solvents and catalysts applied and acetylation evaluation methods.